Pengaruh Penyuluhan ASI Eksklusif Terhadap Pengetahuan Ibu Tentang ASI Eksklusif - Rizka Devi Widya Astuti; Rika Hidayanti; Rizka Devi Widya Astuti; Rosalinda Rosalinda; Salsa Bila; Sita Farahatunnisa; Siti Susanti (WASATHON Jurnal Pengabdian Masyarakat, 2024)
Mother's milk is the best food for babies, considering that the nutritional content in it is very complex and complete. Exclusive breastfeeding coverage in the Rw 5 area of ​​Karngroto Village is still relatively low so there is a need for increased knowledge to increase exclusive breastfeeding coverage. Community service is carried out to increase mothers' knowledge of the importance of exclusive breastfeeding in the RW 05 Karangroto Village area. The method used in this community service activity was outreach using leaflet media and direct demonstrations which were attended by 14 participants. The results of community service activities show that there has been an increase in mothers' knowledge regarding exclusive breastfeeding. It is hoped that this activity can increase insight and knowledge as well as provide support to mothers in providing exclusive breastfeeding.